A Look at the Deadly Shark Attack on an Israeli Diver off the Mediterranean Coast of Hadera, Palestine - Abdel Fattah N. Abd Rabou; Gafar, Maha F.; Mohanna, Aliaa M.; Rafeea, Aysha A.; Jadallah, Rola I.; Rabou, Asmaa A. Abd; Rabou, Ola A. Abd; Shaladan, Reem A.; Benmessaoud, Rimel M.; Cherif, Mourad M.; Fathalli, Afef O; Hamida, Nader Ben Hadj; et al. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The Mediterranean Sea is home to a considerable number of shark species, some of which have posed a threat to humans. The hot waters discharged from the Hadera (Orot Rabin) power plant in northwestern Palestine attract schools of two large coastal shark species: Dusky Sharks (Carcharhinus obscurus Lesueur, 1818) and Sandbar Sharks (Carcharhinus plumbeus Nardo, 1827) every year from November to May. On Monday, April 21, 2025, a 45-year-old Israeli diver was fatally attacked by sharks off the Mediterranean coast of Hadera. The present descriptive study aims to shed light on this rare deadly incident. The study relied on collecting the necessary data through monitoring websites, news, and social media platforms. The Mediterranean coast of Hadera is characterized by a fascinating phenomenon that attracts many beachgoers, as they approach the shallow and warm waters dominated by predatory sharks. Several possible reasons for the shark attack on the Israeli diver have been listed, including the diver's attempt to feed the shark dead fish for filming, the smell of bleeding fish the diver may have been carrying on his belt, mistaken identity of the sharks, the shark's ability to detect the diver's subtle electrical impulses, the diver's possible sudden movements, loud noises, and frantic swimming that attracted the sharks, behavioral changes in the sharks due to human harassment, curiosity and confusion of the shark, hunger and starvation the sharks may have been suffering from, etc. The incident received unprecedented media coverage locally, regionally, and internationally, and sparked widespread interaction on social media platforms. Many Arab posts praised the shark for carrying out the attack, amid the fierce, destructive, and bloody war Israel has been waging against the Gazans since October 7, 2023. To prevent this incident from happening again, there is a need to manage the Mediterranean coast of Hadera in a way that is safe for humans and sharks.